Insider Trading in the Philippines Constitutional and Other Legal Issues on Imposing Civil and Criminal Liability for Short-Swing Profits and Insider Trading Violations (2014)
As of this writing, the Supreme Court has yet to resolve and decide on the merits of a case involving insider trading. It is submitted that this strongly indicates that there is great difficulty in implementing and enforcing prevailing laws and regulations regarding the matter. In this article, the authors present an analysis of the sufficiency and enforceability of key provisions of Republic Act No. 8799, or the Securities Regulation Code, on insider trading, as well as other relevant rules and regulations promulgated by government regulatory agencies. The article, in particular, examines the law and its related rules and regulations in relation to their declared purpose of promoting investor confidence in the Philippines. The article concludes with recommendations of key measures, both legislative and administrative in nature, that may be implemented to ensure the effective realization of the declared policy of the State.
Keywords: Insider trading in securities; Criminal liability; Civil liability; Constitutionalism